What makes professional development effective? Results from a national sample of teachers - Garet, Michael; Porter, Andrew; Desimone, Laura; Birman, Beatrice; Yoon, Kwang Suk (American Educational Research Journal - AMER EDUC RES J, 2001)
This study uses a national probability sample of 1,027 mathematics and science teachers to provide the first large-scale empirical comparison of effects of different characteristics of professional development on teachers’ learning. Results, based on ordinary least squares regression, indicate three core features of professional development activities that have significant, positive effects on teachers’ self-reported increases in knowledge and skills and changes in classroom practice: (a) focus on content knowledge; (b) opportunities for active learning; and (c) coherence with other learning activities. It is primarily through these core features that the following structural features significantly affect teacher learning: (a) the form of the activity (e.g., workshop vs. study group); (b) collective participation of teachers from the same school, grade, or subject; and (c) the duration of the activity.
KerkoCite.ItemAlsoKnownAs: 10.3102/00028312038004915 2339240:Q2BH8PXC 2405685:GTTX33QX

From Preparation to Practice: Designing a Continuum to Strengthen and Sustain Teaching - Feiman-Nemser, Sharon (Teachers College Record: The Voice of Scholarship in Education, 2001)
This paper was written to stimulate discussions and debate about what a professional learning continuum from initial preparation through the early years of teaching could be like. Drawing on a broad base of literature, the author proposes a framework for thinking about a curriculum for teacher learning over time. The paper also considers the fit (or misfit) between conventional approaches to teacher preparation, induction and professional development and the challenges of learning to teach in reform-minded ways and offers examples of promising programs and practices at each of these stages. The paper is organized around three questions: (a) What are the central tasks of teacher preparation, new teacher induction, and early professional development? (b) How well do conventional arrangements address these central tasks? (c) What are some promising programs and practices at each stage in the learning to teach continuum that promote standards-based teaching and enable teachers to become active participants in school reform?